2020
DOI: 10.1038/s41598-020-75553-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome wide SSR discovery cross-taxa transferability and development of marker database for studying genetic diversity population structure of Lilium species

Abstract: Lily belongs to family liliaceae, which mainly propagates vegetatively. Therefore, sufficient number of polymorphic, informative, and functional molecular markers are essential for studying a wide range of genetic parameters in Lilium species. We attempted to develop, characterize and design SSR (simple sequence repeat) markers using online genetic resources for analyzing genetic diversity and population structure of Lilium species. We found di-nucleotide repeat motif were more frequent (4684) within 0.14 gb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…The observed heterozygosity ( Ho ), expected heterozygosity ( He ) and polymorphism information content ( PIC ) was estimated using power marker software version 3 87 , 88 . Further, the dendrogram was constructed on the basis of Nei’s genetic distance matrix using neighbour-joining (NJ) methodology with 1000 bootstrap replicates 28 , 50 , 85 , 89 , 90 . Further, for genetic mapping analysis, tea being a cross pollinated plant species, four alleles representing five different segregation patterns viz.…”
Section: Methodsmentioning
confidence: 99%
“…The observed heterozygosity ( Ho ), expected heterozygosity ( He ) and polymorphism information content ( PIC ) was estimated using power marker software version 3 87 , 88 . Further, the dendrogram was constructed on the basis of Nei’s genetic distance matrix using neighbour-joining (NJ) methodology with 1000 bootstrap replicates 28 , 50 , 85 , 89 , 90 . Further, for genetic mapping analysis, tea being a cross pollinated plant species, four alleles representing five different segregation patterns viz.…”
Section: Methodsmentioning
confidence: 99%
“…Although only a minor portion of the B. rotunda genome at around 0.35%, microsatellites are the key elements in plant genomes. Among these, short sequence repeat mi-crosatellites (SSRs) have found wide utility as co-dominant markers useful in breeding and diversity studies [86,87]. In this study, we identified the genomic and EST-SSRs from B. rotunda, designing primers and showing several to have a transferability to Musa and Ensete genomes, mostly in silico analysis, but with 14 tested in PCR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a minor portion of the B. rotunda genome at around 0.35%, microsatellites are key elements in plant genomes. Among these, short sequence repeat microsatellites (SSRs) have found wide utility as co-dominant markers useful in breeding and diversity studies 85, 86 . In this study, we identified genomic and EST-SSRs from B. rotunda , designing primers and showing several to have transferability to Musa and Ensete genomes, mostly in silico analysis, but with 14 tested in PCR experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Although only a minor portion of the B. rotunda genome at around 0.35%, microsatellites are key elements in plant genomes. Among these, short sequence repeat microsatellites (SSRs) have found wide utility as co-dominant markers useful in breeding and diversity studies 85,86 .…”
Section: Rotundamentioning
confidence: 99%